Research at the University of Holguín: commitment with 2030 Agenda for a sustainable development - León Pupo, Neysi Ileana (2019)
Universities are agents of change looking for spaces in which to promote interdisciplinary research to achieve sustainable lifestyles aimed at achieving the Sustainable Development Goals (SDG) of the 2030 Agenda. In this article, a study of the contribution of the University of Holguin (UHo) in Cuba is carried out, to comply with the SDGs from the current situation of research management in Science, Technology and Innovation (CTI) and its results in the period 2015-2017. A procedure combining qualitative and quantitative analysis was used. Data was recovered through the triangulation of information sources that come from analysis of official documents of the Ministry of Higher Education and the UHo, interviews, observations and statistical analysis. The vice-rector, director and CTI management specialists, president of the scientific advisory council, vice-deans and heads of projects were interviewed. Within the quantitative analysis, the calculation of the Coefficient of Results by Projects indicator is introduced to know the contribution of the projects to the SDGs. The results obtained showed that UHo's biggest contribution is in the objectives of education, economic growth and solid institutions and that opportunities of the environment and the potential of its human capital are not taken advantage of, especially in the topics of renewable energies, water and sanitation, sustainable cities and communities, industry, innovation and infrastructure. This study helps to draw up new strategies that allow the UHo to anticipate the needs of the environment with an innovative mentality.